2015
DOI: 10.1038/cddis.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of RIP1 or RIP3 blockade in murine models of acute liver injury

Abstract: Necroptosis is a recently described Caspase 8-independent method of cell death that denotes organized cellular necrosis. The roles of RIP1 and RIP3 in mediating hepatocyte death from acute liver injury are incompletely defined. Effects of necroptosis blockade were studied by separately targeting RIP1 and RIP3 in diverse murine models of acute liver injury. Blockade of necroptosis had disparate effects on disease outcome depending on the precise etiology of liver injury and component of the necrosome targeted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 51 publications
8
103
3
Order By: Relevance
“…Finally, Casp8 −/− Ripk3 −/− (but not Ripk3 −/− ) mice are highly susceptible to an otherwise sublethal infection with Yersinia pestis as they exhibit reduced levels of various proinflammatory cytokines involved in bacterial control coupled with lower-than-normal death rates of Cd11b + myeloid cells (132). In vitro, such an inhibitory effect was extended to Ripk1 (with Ripk1 −/− fetal liver macrophages and Nec-1 treatment) and linked to inflammasome activation, delineating a Ripk1-, Ripk3-, and Casp8-dependent proinflammatory pathway impinging on core components of the necroptotic machinery (132), which has been confirmed by others (133, 134). The administration of Nec-1 and Nec-1s (a Nec-1 derivative) also limits the demise of Kupffer cells in mice inoculated with Listeria monocytogenes , which restrains both microbicidal inflammation and tissue repair (135).…”
Section: Pathophysiological Relevance Of Necroptosissupporting
confidence: 58%
“…Finally, Casp8 −/− Ripk3 −/− (but not Ripk3 −/− ) mice are highly susceptible to an otherwise sublethal infection with Yersinia pestis as they exhibit reduced levels of various proinflammatory cytokines involved in bacterial control coupled with lower-than-normal death rates of Cd11b + myeloid cells (132). In vitro, such an inhibitory effect was extended to Ripk1 (with Ripk1 −/− fetal liver macrophages and Nec-1 treatment) and linked to inflammasome activation, delineating a Ripk1-, Ripk3-, and Casp8-dependent proinflammatory pathway impinging on core components of the necroptotic machinery (132), which has been confirmed by others (133, 134). The administration of Nec-1 and Nec-1s (a Nec-1 derivative) also limits the demise of Kupffer cells in mice inoculated with Listeria monocytogenes , which restrains both microbicidal inflammation and tissue repair (135).…”
Section: Pathophysiological Relevance Of Necroptosissupporting
confidence: 58%
“…Other studies further demonstrated that ethanol-induced hepatic injury is independent of RIPK1 kinase activity but dependent on RIPK3, suggesting that necroptosis does not always require RIPK1 function (20). A differential damage-dependent requirement of RIPK1 and RIPK3 for induction of liver tissue damage was also supported by another study (21), indicating that, in addition to Although necrosis and necroinflammation are central features of many liver diseases, the role of programmed necrosis in the context of inflammation-dependent hepatocellular death remains to be fully determined. Here, we have demonstrated that the pseudokinase mixed lineage kinase domain-like protein (MLKL), which plays a key role in the execution of receptorinteracting protein (RIP) kinase-dependent necroptosis, is upregulated and activated in human autoimmune hepatitis and in a murine model of inflammation-dependent hepatitis.…”
Section: Introductionsupporting
confidence: 63%
“…Although previous studies have shown that RIPK3 contributes to necrotic cell death after APAP overdose (17,21), oxidative stress-related mitochondrial damage may be closely related to death of hepatocytes in this model (47). This indicates that in hepatocytes several parallel mechanisms exist to execute necrotic cell death in vivo as previously shown in vitro for a variety of other cell types (15).…”
Section: Discussionmentioning
confidence: 75%
“…[15][16][17] Deutsch et al reported that blockading RIP3 ameliorated Concanavalin A-induced hepatitis. 18 However, the premise mechanism still remains elusive and the role of RIP3 in human AIH disease has not yet been reported. As mentioned above, activated macrophages play a crucial role in the development of AIH, therefore we speculated that RIP3 might be involved in the macrophage activation and inflammatory response in AIH.…”
Section: Introductionmentioning
confidence: 99%